Mechanical characterization of hybrid biocomposites reinforced with nonwoven hemp and unidirectional flax fibers - YAYLA, PAŞA (My University, 2023)
Fiber-reinforced polymers are widely used in many applications where high specific strength and high specific stiffness are required. Biocomposites have replaced synthetic-based fiber-reinforced polymers as a preferred option due to their environmental friendliness, ease of supply, and affordability. Comparable strength synthetic-fiber-reinforced polymers and biocomposites both have lower specific weights. This study aims to characterize hybrid biocomposites produced from unidirectional prepregs made of flax/polypropylene fibers and nonwoven mats made of hemp/polypropylene fibers. Research has also been conducted on how the number of layers and the stacking sequence affect the mechanical performance of hybrid biocomposites. Three different designs of biocomposite plates have been produced using compression molding. They were then subjected to tensile, compressive, shear, bending, Charpy impact, and drop-weight impact tests. According to the test results, it is found that each design has its own characteristics, and the characterized static and dynamic behaviors are very different from each other. Therefore, each biocomposite mentioned here may be a good candidate for engineering design based on the given engineering design criteria.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; MALZEME BİLİMİ, SERAMİK; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; MATERIALS SCIENCE, CERAMICS; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; Seramik ve Kompozitler; Fizik Bilimleri; Genel Kimya; Polimerler ve Plastikler; Malzeme Kimyası; Ceramics and Composites; Physical Sciences; General Chemistry; Polymers and Plastics; Materials Chemistry; biocomposites; flax fiber; hemp fiber; mechanical characterization